A pro‐tumourigenic loop at the human prostate tumour interface orchestrated by oestrogen, CXCL12 and mast cell recruitment. Issue 1 (9th July 2014) - Ellem, Stuart J; Taylor, Renea A; Furic, Luc; Larsson, Ola; Frydenberg, Mark; Pook, David; Pedersen, John; Cawsey, Bree; Trotta, Andrew; Need, Eleanor; Buchanan, Grant; Risbridger, Gail P
Abstract Prostate cancer is hormone‐dependent and regulated by androgens as well as oestrogens. The tumour microenvironment also provides regulatory control, but the balance and interplay between androgens and oestrogens at the human prostate tumour interface is unknown. This study reveals a central and dominant role for oestrogen in the microenvironment, fuelling a pro‐tumourigenic loop of inflammatory cytokines involving recruitment of mast cells by carcinoma‐associated fibroblasts (CAFs). Mast cell numbers were increased in human PCa clinical specimens, specifically within the peritumoural stroma. Human mast cells were also shown to express ERα and ERβ, with oestradiol directly stimulating mast cell proliferation and migration as well as altered cytokine/chemokine expression. There was a significant shift in the oestrogen:androgen balance in CAFs versus normal prostatic fibroblasts (NPFs), with a profound increase to ER:AR expression. Androgen signalling is also reduced in CAFs, while ERα and ERβ transcriptional activity is not, allowing oestrogen to dictate hormone action in the tumour microenvironment. Gene microarray analyses identified CXCL12 as a major oestrogen‐driven target gene in CAFs, and CAFs recruit mast cells via CXCL12 in a CXCR4‐dependent manner. Collectively, these data reveal multicellular oestrogen action in the tumour microenvironment and show dominant oestrogen, rather than androgen, signalling at the prostatic tumour interface. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.